2013
DOI: 10.1111/apa.12273
|View full text |Cite
|
Sign up to set email alerts
|

B‐type natriuretic peptide for assessment of haemodynamically significant patent ductus arteriosus in premature infants

Abstract: Aim: Haemodynamically significant patent ductus arteriosus (hsPDA) is frequently observed in premature infants. This study was conducted to explore whether the blood BNP can be a valuable biomarker to assess the necessity of treatment for hsPDA in premature infants.Methods: Serial measurements of the blood BNP were performed during the first 5 days of life in premature infants with hsPDA (Group I) and those without hsPDA (Group N). The definition of the hsPDA was the PDA requiring treatment, such as indomethac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
4
19
0
5
Order By: Relevance
“…In children, BNP levels have been studied in the setting of congenital heart disease [3] and patent ductus arteriosus (PDA) [11], as well as persistent pulmonary hypertension of the newborn (PPHN) [4]. Serum BNP levels are significantly increased in patients with hemodynamically symptomatic PDA requiring indomethacin administration and/or surgical ligation compared to those with asymptomatic PDA [12]. In this setting, BNP levels may have predictive value in determining those infants likely to develop hemodynamic changes necessitating treatment [13].…”
Section: Discussionmentioning
confidence: 99%
“…In children, BNP levels have been studied in the setting of congenital heart disease [3] and patent ductus arteriosus (PDA) [11], as well as persistent pulmonary hypertension of the newborn (PPHN) [4]. Serum BNP levels are significantly increased in patients with hemodynamically symptomatic PDA requiring indomethacin administration and/or surgical ligation compared to those with asymptomatic PDA [12]. In this setting, BNP levels may have predictive value in determining those infants likely to develop hemodynamic changes necessitating treatment [13].…”
Section: Discussionmentioning
confidence: 99%
“…The increased pulmonary flow also leads to left heart overload. Thus, the utility of NT-proBNP levels as a biomarker for screening, diagnosis, and monitoring of ductus patency is physiologically explained by the increases occurring in this parameter in situations of hemodynamic overload with stretching of the myocardial wall [5,10,18,21]. In a previous study [19], we found a strong association between HS-PDA and increased NT-proBNP levels, with a specificity of 100 %; that is, patients with an NT-proBNP value above the cutoff level of 9321.5 pg/mL will have HS-PDA [19].…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, echocardiography was performed by a pediatric cardiologist blinded to the NT-proBNP results at the time of the examination, using an Aloka ProSound Alpha7 system (Hitachi, Tokyo, Japan). The following criteria defined a clinically significant PDA: ductus diameter > 1.5 mm, retrograde diastolic flow in the descending aorta > 30 %, increased left atrial (LA) distension (LA/aorta ratio > 1.4), and transductal Doppler speed < 2 m/s [18]. Management of clinically significant PDA was carried out according to our Neonatal Unit guidelines: medical treatment with ibuprofen (first dose 10 mg/kg, second and third doses 5 mg/kg, separated by 24 h), and surgical ligation for patients in whom medical treatment failed or was contraindicated [13,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…показали (31 недоношенный, средний гестационный возраст 30 нед), что при превышении уровня BNP > 1805 пг/мл медикаментозное лечение ГЗФАП является неэффективным и требуется последующее хирургическое лечение [43]. Рефрактерность к медикаментозному закрытию ГЗФАП установлена и при увеличении BNP > 2000 пг/мл (46 недоношенных, гестационный возраст < 33 нед, масса тела < 1500 г) [44]. Кроме того, отмечено, что лигирование ГЗФАП при высоких значениях BNP позволяет уменьшить количество курсов НПВП у таких пациентов и способствует снижению числа осложнений, связанных с терапией НПВП [44].…”
Section: физиология и патофизиология натрийуретических пептидовunclassified